A systematic review of marital satisfaction and psychological well-being among career women - Wan Othman, Wan Norhayati; Nor Zainudin, Zaida; Mohamad Yusop, Yusni; Wan Jaafar, Wan Marzuki; Mokhtar Baxodirovna, Muhammad Yasin Omar (Gokmen Arsian, 2022)
Marital satisfaction is always related to the psychological well-being of career women. Career women with a high level of work satisfaction will have better marital satisfaction and psychological well- being. This review aims to look for the relationship between marital satisfaction and psychological well-being among career women. Scopus, ScienceDirect and PubMed database was selected to identify relevant articles. Research published between the year 2012 to 2021 was selected to look at the effect of employment on marital satisfaction and psychological well-being and the relationship between marital satisfaction and psychological well-being. The finding shows that employed women will have better marital status compared to those who are housewives. They have greater financial freedom and self-direction. Additionally, emotional stability affects women’s marital satisfaction and psychological well-being. Additionally, marital intimacy is critical for marital satisfaction and psychological well-being maintenance. The article’s implications are also discussed in terms of how the counsellor might enhance their counselling service to assist career women in achieving optimal psychological well-being and marital satisfaction.